2013
DOI: 10.2355/isijinternational.53.1187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Swirling Flow in Submerged Entry Nozzle on Square Billet Continuous Casting of Steel Process

Abstract: In this study, a new method for swirling flow generation in submerged entry nozzle (SEN) in continuous casting of steel process has been proposed. A rotating electromagnetic field is set up around the SEN to induce swirling flow in it by the Lorentz force. And this kind of electromagnetic swirling flow in the SEN is proposed to use in square billet continuous casting of steel process. The effects of coil current intensity and nozzle structure on the flow and temperature fields in the SEN and mold are numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…[27,28] In addition, previous studies show that a strong swirling steel flow can be obtained in the SENs and in molds. [27][28][29][30][31][32][33][34][35] This means that the technologies for a swirling flow in the SENs has the potential to replace the electromagnetic stirring in molds. [10,11,36,37] The swirling flow inside the SEN was probably first proposed by Yokoya et al [29] in 1994.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[27,28] In addition, previous studies show that a strong swirling steel flow can be obtained in the SENs and in molds. [27][28][29][30][31][32][33][34][35] This means that the technologies for a swirling flow in the SENs has the potential to replace the electromagnetic stirring in molds. [10,11,36,37] The swirling flow inside the SEN was probably first proposed by Yokoya et al [29] in 1994.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, many studies have been carried out to investigate the steel flow phenomena in molds, for both the slab and the billet casting, using a swirling flow in SENs. [27][28][29][30][31][32][33][34][35] This is a way to control the steel flow in molds in a root manner by optimizing the SEN port flow with a rotational velocity component. Overall, two methods have mainly been investigated to produce a swirling flow in SENs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier research, it has been shown that a swirl flow helps to control a flow pattern in a mold. Consequently, it was acknowledged that a swirl flow enhances the heat and mass transfer and improves the superheat dissipation in a melt.…”
Section: Introductionmentioning
confidence: 99%
“…25,26,28,29,31,32) The swirling flow is obtained by installing the electromagnetic stirring equipment outside the SEN. Simulation results 25,29,31,32) showed that it can produce a good swirling flow inside the SEN. However, it requires an equipment cost and an electricity cost.…”
Section: )mentioning
confidence: 99%